Virtue Depends on Natural Law and Divine Commands - J. Caleb Clanton; Kraig Martin (Religions)
Virtue theory has occupied a place of relative prominence within the Christian intellectual tradition. But there is a problem facing it: how one contemplates the virtues and vices will ultimately depend upon deeper accounts of the good and the right. Accordingly, virtue theory is incomplete, at least when taken by itself. Our task in this paper is to show that neither of the standard approaches to explaining the metaphysical foundations of morality within the Christian tradition—natural law theory and divine command theory—are sufficient to fix this incompleteness. We thus propose a combination of natural law theory and divine command theory to remedy the matter. The upshot of our argument, then, is this: what counts as a virtue ultimately depends upon the natural law and divine commands.